Closing the Loop - From Research on Natural Resources to Policy Change - Tabor, Steven R.; Faber, Doeke C. (International Service for National Agricultural Research, 1998)
Sustainable management of natural resources in agriculture is a goal shared by all nations. Achieving this goal may require a great number of changes in the way natural resources are allocated, utilized and regulated. Both science and public policy have key roles in enhancing the sustainability of natural resource use. The greater the degree of cooperation between the two, the better the prospects that suitable solutions to resource management challenges will be found. In November 1997, ECDPM and ISNAR hosted an expert consultation that brought together the experiences of policy makers, donor agencies and non-governmental organizations in bridging the gap between science and resource management change. The results of this meeting make up this book.